A Comparative Analysis of the Endocannabinoid System in the Retina of Mice, Tree Shrews, and Monkeys. (8th February 2016) - Bouskila, Joseph; Javadi, Pasha; Elkrief, Laurent; Casanova, Christian; Bouchard, Jean-François; Ptito, Maurice
Abstract : The endocannabinoid (eCB) system is widely expressed in various parts of the central nervous system, including the retina. The localization of the key eCB receptors, particularly CB1R and CB2R, has been recently reported in rodent and primate retinas with striking interspecies differences. Little is known about the distribution of the enzymes involved in the synthesis and degradation of these eCBs. We therefore examined the expression and localization of the main components of the eCB system in the retina of mice, tree shrews, and monkeys. We found that CB1R and FAAH distributions are well-preserved among these species. However, expression of NAPE-PLD is circumscribed to the photoreceptor layer only in monkeys. In contrast, CB2R expression is variable across these species; in mice, CB2R is found in retinal neurons but not in glial cells; in tree shrews, CB2R is expressed in Müller cell processes of the outer retina and in retinal neurons of the inner retina; in monkeys, CB2R is restricted to Müller cells. Finally, the expression patterns of MAGL and DAGL α are differently expressed across species. Overall, these results provide evidence that the eCB system is differently expressed in the retina of these mammals and suggest a distinctive role of eCBs in visual processing.